Comparison of the In Vitro Activities of HR756 with Cephalothin, Cefoxitin, and Cefamandole - Sosna, Jacob P. (1978)
The in vitro activity of HR756, a new semisynthetic cephalosporin, was compared with the activities of cephalothin, cefoxitin, and cefamandole against 1,535 isolates of gram-positive and gram-negative bacteria. HR756 was less active than cephalothin and cefamandole and twofold more active than cefoxitin against Staphylococcus. All four of the antibiotics were inactive against the enterococcus group of Streptococcus; however, HR756 was the most active antibiotic against the other isolates of Streptococcus. HR756 was also more active against isolates of Enterobacteriaceae, including 84 to 95% of the isolates resistant to one or more of the other three antibiotics. HR756, at a concentration of 12.5 μg/ml, inhibited 86, 75, and 100% of the isolates of Pseudomonas aeruginosa, other Pseudomonas species, and Acinetobacter, respectively. The minimal inhibitory concentrations and minimal bactericidal concentrations of HR756 were within one twofold dilution for 11 of 21 gram-positive cocci and 119 of 125 gram-negative bacilli tested.